P1_1 The Fate of the Falling Feline - Dexter, Katie; Connors, Riley; Argyle, Joshua; Scoular, Cameron (Physics Special Topics, 2012)
This article considers the potential energy of a falling cat and explores the maximum height from which the fall can occur without sustaining limb fractures, taking into account the drag due to air resistance. 2.3m was found to be the highest distance from which a cat can fall without fracturing all four of its legs. However, investigations into the typical number of limb fractures sustained indicated that cats are able to fall from greater heights. This is due to the assumptions made; cats have only one bone in their legs and their muscles do not contract upon landing.